Memoria E impunidad a través del imaginario cinematográfico: La mujer sin cabeza (Lucrecia martel, 2008) y El secreto de sus ojos (Juan José Campanella, 2009) (Revista de Crítica Literaria Latinoamericana, 2011)
This article explores the connection between the Argentine films The Headless Woman (Lucrecia Martel, 2008) and The Secret in Their Eyes (Juan José Campanella, 2009). Both works show the tension created by the laws of impunity following the Dirty War in Argentina in the seventies and eighties. Both films probe the manner in which the civil law was contaminated by actions taken on political crimes, even decades after the events. The characters of these films have a complex perception of justice, distorted by the terrible impact of the crimes against humanity and breaches of justice. The immediate consequence was the devaluation of human life, and feelings of guilt and pain of the characters in both films, while witnessing the complex struggle between memory and forgetting.
Keywords: Justice; Dirty War; Argentina; Memory; Forgetting